EVALUATION COEFFICIENT OF CONSOLIDATION IN PVD AND SOIL PRELOADING IN CLUSTER F SUMMARECON BANDUNG - Zhafira Anggraeni Nurwanda; Moch. Sholeh (Jurusan Teknik Sipil Politeknik Negeri Malang, 2026)
This thesis evaluates the horizontal coefficient of consolidation (Ch) in a soft soil improvement project using Prefabricated Vertical Drains (PVD) and preloading at Cluster F, Summarecon Bandung. The area consists of soft clay with high compressibility and low shear strength, requiring ground improvement for safe construction. The study compares the assumed Ch value used in design with the actual Ch obtained from field monitoring. The design Ch was derived from laboratory consolidation tests and applied using Barron’s radial consolidation theory. Settlement plate data collected during preloading was analyzed with the Asaoka method to calculate the actual Ch. Results show a clear discrepancy: the assumed Ch of 2.93 × 10⁻⁴ m²/s was significantly higher than the actual Ch of 1.60 × 10⁻⁴ m²/s, a deviation of -45%. This indicates that relying solely on laboratory values can lead to overly optimistic settlement predictions. Using the actual Ch in revised analysis produced more realistic results. The study highlights the importance of validating design parameters with field data, as back-calculation from monitoring provides better insight into soil behavior, reduces construction risks, and leads to more reliable ground improvement designs.